Organic cultivation of Palam Basmati 01 A new hope for paddy farmers of West Sikkim - Limboo, Til Kumari; Dulal, Jaya Prakash (Indian Farming, 2025)
The organic cultivation of Palam Basmati 01 (HPR-2612) in West Sikkim has offered new hope for local paddy farmers, providing a profitable and sustainable alternative to traditional rice varieties. With the support and guidance of Krishi Vigyan Kendra (KVK), farmers like Shri Indra Bdr. Chettri successfully cultivated this semi-scented, high-yielding variety, achieving a yield of 38.5 q/ha andsubstantial income gains. The KVK organized training, demonstrations, and awareness programs that introduced farmers to sustainable practices such as seed treatments with Trichoderma viridis to enhance crop protection. The success of the initial trials inspired other farmers to adopt Palam Basmati, leading to increased demand and government-supported seed distribution. This initiative underscores the potential for organic Basmati rice to enhance the socio-economic well-being of farmers in Sikkim through sustainable and profitable agriculture.